Life. the science of biology / William K. Purves - Purves, William K. (1992)
The science of biology, characteristics of living organisms, the methods of science, the cell, small molecules, large molecules; organization of the cell, membranes, energy, enzymes, and catalysis, pathways that release energy in cells, photosynthesis; information and heredity, mendelian genetics and beyond, nucleic acids the genetic material, molecular genetics of prokaryotes, gene expression in eukaryotes, recombinant DNA technology, animal development immunes and disease; evolutionary processes, the mechanisms of evolution, the multiplication of species, the evolution of reproductive isolation, systematics and phylogeny; the evolution of diversity viruses and monera, Protista, fungi, plants, sponges and protostomate animals, deuterostomate animals, pattrns in the evolution of life; the biology of flowering plants, transport, support, and protection, plant nutrition, reproduction and development in flowering plants; physiology, homeostasis, and the regulation, animal hormones, animal reproduction; ecology and biogeography, behavioral ecology, structure and dynamics of population, interaction within biological communities.